PENGARUH KOMISARIS INDEPENDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK - Mishelei Loen, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to determine the effect of partial or simultaneous independent commissioners and institutional ownership on tax aggressiveness. `The data used in this research is secondary data. The data sources used in this study were obtained from the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2020 period, which were downloaded from the Indonesia Stock Exchange website, namely www.idx.co.id, which would then be processed using the SPSS version of the software. 25. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2020 period. The number of samples observed was 194 data with an observation period of 2 (two) years from 2019–2020. The test results show that the independent commissioner has a negative effect on tax aggressiveness. Institutional ownership has a negative effect on tax aggressiveness, and independent commissioners and institutional ownership have a simultaneous negative effect on tax aggressiveness.